LUNG FUNCTION AND COGNITIVE PERFORMANCE OF PRIMARY SCHOOL CHILDREN EXPOSED TO SECONDHAND SMOKE AT HOME IN KOTA BHARU, KELANTAN - Sharina D; Zulkifli A; Naing NN (Malaysian Journal of Public Health Medicine, 2004)
Ex/>osure to secondhand smoke has consistently been linked to adverse health effects in children, including reduced lung function and various respiratory diseases. There is also increasing evidence that secondhand smoke exposure is associated with cognitive impairment and behavioral problems in children. This cross sectional study was done on 795 children to determine the association between secondhand smoke exposure and peak expiratory flow rate ( PEFR) and cognitive performance among the primary school children in Kota Bharu Kelantan. A questionnaire was used to obtain information on socio